Interpolation and shock persistence of prewar U.S. macroeconomic time series: A reconsideration - Hashem Dezhbakhsh; Daniel Levy (Economics Letters, 2022)
The U.S. prewar output series exhibit smaller shock-persistence than postwar-series. Some studies suggest that this may be due to linear interpolation used to generate missing prewar data. Monte Carlo simulations that support this view generate large standard-errors, making such inference imprecise. We assess analytically the effect of linear interpolation on a nonstationary process. We find that interpolation indeed reduces shock-persistence, but the interpolated series can still exhibit greater shock-persistence than a pure random walk. Moreover, linear interpolation makes the series periodically nonstationary, with parameters of the data generating process and the length of the interpolation time-segments affecting shock-persistence in conflicting ways.
Keywords: C01; C02; E01; E30; N10; 330; Linear Interpolation; Random Walk; Shock Persistence; Nonstationary Time Series; Periodic Nonstationarity; Stationary Time Series; Prewar US Time Series; Prewar vs Postwar Business Cycles